Le débat entre Adorno et Sohn-Rethel - Agnès Grivaux (Recherches Germaniques)
The point of departure for this article is the dialog between Adorno and Sohn-Rethel, initiated in 1936, concerning the latter’s presentation on the sociological theory of knowledge (Luzerner Exposé). It will highlight a neglected aspect of the Adornian debate with Sohn-Rethel regarding the theory of knowledge: these discussions took place against the backdrop of the controversy over psychologism, which is indispensable to have in mind to be able to properly understand them. The article shows that Adorno is especially interested in the fact that Sohn-Rethel’s theory manages to lay the foundations of a third way for the theory of social knowledge: its original articulation of genesis and validity can clarify the relationship between forms of knowledge and social relations.